Association between HMG CoA reductase inhibitors and anxiety:an experimental study using elevated plus maze and light dark arena behavioural models - Gudadappanavar, Anupama M.; Hombal, Prashant R. (International Journal of Research in Medical Sciences, 2017)
Background: Aims: To investigate the effect of HMG CoA reductase inhibitors on behavioural models of anxiety in male swiss mice using Elevated plus maze test and light-dark arena test. Methods: It was an experimental study, carried out in department of Pharmacology, J. N. Medical College, KLE University, Belgaum. The in vivo behavioural activity of simvastatin, lovastatin, atorvastatin was studied using EPM and light-dark arena test. The mice received the drugs as per their weight and subjected for experimentation. Group mean time spent and number of entries into open arm in EPM test and group mean number of entries and time spent in the light area was calculated in treated and control groups for comparison. Statistical analysis was done using ANOVA followed by Bonferroni’s multiple comparison test (P<0.05). Results: Going through the results of this study an evidence for the association between lowered serum cholesterol and symptoms of anxiety can be seen as statins used in the present study failed to show significant anxiolytic effect when compared to standard but in turn showed even more less activity when compared to control, indicating anxiogenic behavior. Conclusions: Our findings support the evidence of the negative effects of statins on psychological outcomes. It’s generally understood that having low cholesterol is a good health sign, combined with other factors; it could actually put a person at risk by causing anxiety and stress. Further research comprising a greater number of studies is required to confirm the effects of this agent on psychological outcomes.